2014
DOI: 10.3109/13880209.2013.876653
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress inGlinus oppositifoliusresearch

Abstract: In clinical practice, the plant has been extensively investigated in a broad range of studies to provide scientific evidence for folklore claims or to find new therapeutic uses. The present review may arouse related research and make a more valid display for Taiwanese native medicinal plants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 11 publications
0
22
0
2
Order By: Relevance
“…Combing through the literature has shown that the plant has been traditionally used for various purposes since a long time. In Mali, hot water extract of aerial part has been traditionally used as a medicine to heal wounds, while decoction of aerial part has been known to possess an anti-malarial effect [8][9][10][11][12][13]. Glinus extracts are also used for relief from joint pain, inflammations, diarrhoea, intestinal parasites, fevers, boils and skin disorders [13,14].…”
Section: Page | 544 |mentioning
confidence: 99%
See 4 more Smart Citations
“…Combing through the literature has shown that the plant has been traditionally used for various purposes since a long time. In Mali, hot water extract of aerial part has been traditionally used as a medicine to heal wounds, while decoction of aerial part has been known to possess an anti-malarial effect [8][9][10][11][12][13]. Glinus extracts are also used for relief from joint pain, inflammations, diarrhoea, intestinal parasites, fevers, boils and skin disorders [13,14].…”
Section: Page | 544 |mentioning
confidence: 99%
“…In Mali, hot water extract of aerial part has been traditionally used as a medicine to heal wounds, while decoction of aerial part has been known to possess an anti-malarial effect [8][9][10][11][12][13]. Glinus extracts are also used for relief from joint pain, inflammations, diarrhoea, intestinal parasites, fevers, boils and skin disorders [13,14]. It is also used in treatment of jaundice [13,15], and hepatitis [13,16].…”
Section: Page | 544 |mentioning
confidence: 99%
See 3 more Smart Citations